2021
DOI: 10.1101/2021.03.17.435799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Default Mode Network spatial configuration varies across task domains

Abstract: Recent developments in network neuroscience suggest reconsidering what we thought we knew about the Default Mode Network (DMN). Although this network has always been seen as unitary and associated with the resting state, a new deconstructive line of research is pointing out that the DMN could be divided into multiple subsystems supporting different functions. By now, it is well known that the DMN is not only deactivated by tasks, but also involved in affective, mnestic, and social paradigms, among others. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 233 publications
(294 reference statements)
0
4
0
Order By: Relevance
“…While previous work suggests a strong anti-correlation between the canonical DMN and the FPCN, DAN, and CON is related to better CC task performance, to our knowledge these studies have not investigated the relationship between the FPCN subnetworks and dorsal-DMN [34]. Investigating how these networks are related to one another at rest and when performing CC tasks in individuals may help researchers to understand the complex functional diversity of the DMN and the FPCN.…”
Section: The Default Mode Network (Dmn)mentioning
confidence: 85%
See 2 more Smart Citations
“…While previous work suggests a strong anti-correlation between the canonical DMN and the FPCN, DAN, and CON is related to better CC task performance, to our knowledge these studies have not investigated the relationship between the FPCN subnetworks and dorsal-DMN [34]. Investigating how these networks are related to one another at rest and when performing CC tasks in individuals may help researchers to understand the complex functional diversity of the DMN and the FPCN.…”
Section: The Default Mode Network (Dmn)mentioning
confidence: 85%
“…Activity within the DMN is frequently associated with the brain at rest (i.e., not participating in a goal-directed task) [56][57][58]. However, recent studies revealed that the DMN was active during other functions, which included introspective thinking [59], spontaneous cognition [60], working memory processing [61], creative problem solving/ divergent thinking [25], semantic memory processing [62], and task switching [34,63]. Like the FPCN, the DMN also contains multiple distinct networks including: a midline network (canonical DMN behavior, i.e., mind-wandering) and a lateral component (associated with externally mediated tasks requiring internal mentation (i.e., task switching) [34,56,57,[62][63][64][65][66][67]).…”
Section: The Default Mode Network (Dmn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neurodegeneration poses a significant challenge for the fields of neuroscience and medicine, as it is the underlying cause of the development and advancement of numerous neurodegenerative and psychiatric disorders [1][2][3]. It encompasses the progressive decay and loss of neurons across various levels of organization, ranging from molecular to network levels [4][5][6][7]. Onset can manifest at various life stages, ranging from early phases, as observed in neurodevelopmental disorders, to later stages, exemplified by conditions like Alzheimer's disease (AD) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%